2015
DOI: 10.1073/pnas.1521740112
|View full text |Cite
|
Sign up to set email alerts
|

Ezh2 regulates differentiation and function of natural killer cells through histone methyltransferase activity

Abstract: Changes of histone modification status at critical lineage-specifying gene loci in multipotent precursors can influence cell fate commitment. The contribution of these epigenetic mechanisms to natural killer (NK) cell lineage determination from common lymphoid precursors is not understood. Here we investigate the impact of histone methylation repressive marks (H3 Lys27 trimethylation; H3K27 me3 ) on early NK cell differentiation. We demonstrate that selective loss of the histone-lysine N-methyltransferase Ezh2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
124
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(135 citation statements)
references
References 39 publications
4
124
1
Order By: Relevance
“…2A). Our results differed from a prior study that reported a modest increase in NK cell number in the spleen of Vav1 cre Ezh2 fl/fl mice(37). In competitive chimeras, Ezh2 Δ/Δ bone marrow NK cells were present and splenic NK cell numbers were expanded when compared to controls, indicating that EZH2 limits NK cell expansion or survival (Fig.…”
Section: Resultscontrasting
confidence: 99%
“…2A). Our results differed from a prior study that reported a modest increase in NK cell number in the spleen of Vav1 cre Ezh2 fl/fl mice(37). In competitive chimeras, Ezh2 Δ/Δ bone marrow NK cells were present and splenic NK cell numbers were expanded when compared to controls, indicating that EZH2 limits NK cell expansion or survival (Fig.…”
Section: Resultscontrasting
confidence: 99%
“…EZH2: -1.2 fold, PCAF: +4.8 fold, P300: +1.9 fold). We subsequently focused on studying the role of EZH2, a key writer of the histone code that enzymatically mediates the H3K27Me3 repressive mark and, in several contexts, antagonizes cell differentiation by acting as an epigenetic barrier[3739]. We hypothesized, that if functional under the conditions studied here, EZH2 can work as a barrier to cholangiocyte differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…One study showed that EZH2 expression is induced upon activation of rat hepatic stellate cells, and that the EZH2 inhibitor, 3-deazaneplanocin A, impairs stellate cell activation. EZH2 inhibitors have also been demonstrated to stimulate the effectiveness of natural killer cells [121]. Notably, EZH2 inhibitors can inhibit the antitumorigenic activities of T cells [101].…”
Section: Opportunities To Epigenetically Remodel Stromal Cellsmentioning
confidence: 99%